THE USE OF ANTERIOR AND POSTERIOR COLON GASTROJUNOANASTOMOSES IN GASTROPANCREATODUODENAL RESECTION (Conferencea, 2024)
By studying the results of anterior and posterior colon gastrojunoanastomoses, to determine a useful reconstruction method to minimize the frequency of delayed gastric emptying (DGE) and other complications after GPDR.